Implementation of Guided Inquiry Learning with a Scientific Approach to Improve Class VII Middle School Students' Science Process Skills on Density Material - Ela Nurlaela (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to look at the implementation of learning using the guided inquiry model using a scientific approach in one of the classes at Al Azhar 3 Bintaro Islamic Middle School. Apart from that, this research also aims to see the improvement in junior high school students' science process skills after implementing the guided inquiry learning model. This research is Classroom Action Research (PTK) with 2 cycles. Each cycle consists of planning, implementing actions, observing and reflecting. The instruments used consisted of essay questions, e-LKPD, student observation sheets, observation sheets on the implementation of learning using guided inquiry, and practical video assessment rubrics that students created as a form of communicating the results of the investigation, which were then uploaded to social media. The research results showed that after implementing the guided inquiry learning model, all indicators of students' process skills experienced an average increase of 16%.